Lavagem de dinheiro : a tutela penal sobre a transparência da ordem econômica - Rocha Neto, Tapir Tabajara Canto da (2016)
This work is inserted in the search line Legal and Criminal Contemporaries Systems under the guidance of Prof. Dr. Giovani Agostini Saavedra. The present work suggest a dogmatic and critical analysis in respect to promulgation of Law number 12.683/2012, especially in relation to problematic issues from extinction, of the Brazilian legal system, the list of predicate crimes that can generate money laundry. A superficial reading of the new law would allow the understanding that any form of conduct positively as a criminal offense would have aptitude for materialization the money laundering crime, simply if the profit earned by an offense or a misdemeanor was hidden or concealed. From the examination about Axel Honneth’s Theory of Recognition and the current context in which inserted the global economy, the dissertation intends to establish that we can only speak in money laundry if there is an offense to the transparency of developed financial relations as part of an order capitalist economic and democratic.